The mechanical properties of concrete contains palm oil clinker as coarse aggregate replacement and POFA as cement replacement - Abdullah, Afan Mohammed Salah (2019)
The usage of agricultural waste in form of ashes as one of the constituent materials in concrete has been done through the years The dumping of POC in growing quantity throughout the years worsen the environmental pollution, consumes larger disposal area and increases the cost spent by the palm oil mill in managing the waste. The main aim of this research is to study the mechanical performance of concrete containing palm oil clinker as partial course aggregate replacement with fix percentage and palm oil fuel ash as cement replacement the increasing aggregate and cement mining activity to due to growth of construction industry in Malaysia, demand toward construction material. In addition, the escalation of palm oil clinker (POC) and POFA disposal from Malaysian palm oil industry have caused negative impact to the environment quality. The objectives of this study are to investigate the effect of palm oil clinker as partial course aggregate replacement and POFA as partial cement on workability, compressive, flexural strength. Generally, there are three different percentages of POFA replacement in concrete mixture, which are 0%, 5%, and 10% respectively of palm oil fuel ash and fix percentage of POC, which is 25% in all mix. For compressive strength test and flexural test, the concrete are tested on 7, and 28 days. The same mixture also, was used to conduct module of elasticity test and tensile test. The concrete mixture was designed according to British standard with water cement ratio of 0.45. For compressive strength test, 24 cubes size 150mm x 150mm x 150mm were tested on 7, and 28 days each. Meanwhile, for flexural test, 24 concrete beam size 100mm x 100mm x 500mm been tested on 7, and 28 days for each test. Not to forget the slump test also was conducted for fresh concrete test. This research reveals the usage of POFA in concrete mixture can improve the compressive strength test and acoustical properties specifically for sound insulation. But the usage of POFA in concrete mixture strictly must not exceed 10% as it will decrease the performance of the concrete strength on the other hand the best percentage for palm oil clinker as course aggregate partial replacement is 25% otherwise will lead to decrease compressive and flexural strength